2015
DOI: 10.5719/hgeo.2015.92.4
|View full text |Cite
|
Sign up to set email alerts
|

Geodemographic analysis of tuberculosis patients in Karachi, Pakistan

Abstract: Tuberculosis (TB) is endemic in Karachi, Pakistan, and even with the discovery of other infectious diseases no signicant change is evident in its epidemiological prole while analyzing the temporal incidence. There is signicant evidence to support the fact that poverty is the leading cause of TB. A number of scholarly analyses have documented associations among patients' characteristics (sex, age group); social factors (education, origin of the patient, smoking, alcohol and drug use); environmental factors (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Some studies found that there was a relationship between tuberculosis and educational status (Abdallah & Ali 2012;Harling, G., Ehrlich & Myer 2008;Hussain, H, Akhtar & Nanan 2003;Jethani et al 2013;Jurcev-Savicevic et al 2013;Kaulagekar & Radkar 2007;Miandad et al 2015;Tesema et al 2015). The others studies reveal that illiteracy was a risk factor contributing to tuberculosis dissemination (Shafee et al 2013).…”
Section: Educational Statusmentioning
confidence: 99%
See 4 more Smart Citations
“…Some studies found that there was a relationship between tuberculosis and educational status (Abdallah & Ali 2012;Harling, G., Ehrlich & Myer 2008;Hussain, H, Akhtar & Nanan 2003;Jethani et al 2013;Jurcev-Savicevic et al 2013;Kaulagekar & Radkar 2007;Miandad et al 2015;Tesema et al 2015). The others studies reveal that illiteracy was a risk factor contributing to tuberculosis dissemination (Shafee et al 2013).…”
Section: Educational Statusmentioning
confidence: 99%
“…There was a relationship between TB and inadequate housing (Jurcev-Savicevic et al 2013). The others studies found that tuberculosis has a positive asociation with household hygiene and poor ventilation (Harling, G., Ehrlich & Myer 2008;Kiboss & Kibitok 2003;Miandad et al 2015;Taher-Ghasemi et al 2016;Tesema et al 2015). Furthermore, some studies reveal that the risk of TB was increased because of crowding in the household (Firdaus & Ahmad 2013;Gyawali et al 2012;Kiboss & Kibitok 2003;Kibret et al 2013;Shafee et al 2013;Sial et al ;Tesema et al 2015).…”
Section: Inadequate Housingmentioning
confidence: 99%
See 3 more Smart Citations